2020
DOI: 10.3390/nu12092889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Magnesium Content on Intestinal Microbiota of Rats

Abstract: Background: Magnesium is a mineral that modulates several physiological processes. However, its relationship with intestinal microbiota has been scarcely studied. Therefore, this study aimed to assess the role of dietary magnesium content to modulate the intestinal microbiota of Wistar male rats. Methods: Rats were randomly assigned one of three diets: a control diet (C-Mg; 1000 mg/kg), a low magnesium content diet (L-Mg; 60 mg/kg), and a high magnesium content diet (H-Mg; 6000 mg/kg), for two weeks. After tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Though a content of 0.05% has been extensively used as normal in rat experimental studies, a slightly higher dietary concentration might be required if the experimental conditions might affect the absorption of Mg. A high dietary phosphate content can reduce the absorption and/or availability of Mg, and a decreased magnesium absorption is often found in renal disease 33 . Similarly to our conditions, the contents of 0.1% or around have been also established as the normal levels in many studies addressing dietary Mg supplementation, in which a 0.6% Mg was also given as a high Mg diet 34‐37 . Our results showed that in the uraemic rats fed a normal Mg (0.1%) a systemic inflammatory response was induced, as deduced from the elevation in the plasma of the pro‐inflammatory cytokines TNF‐α, IL‐1β and IL‐6, which are related to acute‐phase responses and inflammation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Though a content of 0.05% has been extensively used as normal in rat experimental studies, a slightly higher dietary concentration might be required if the experimental conditions might affect the absorption of Mg. A high dietary phosphate content can reduce the absorption and/or availability of Mg, and a decreased magnesium absorption is often found in renal disease 33 . Similarly to our conditions, the contents of 0.1% or around have been also established as the normal levels in many studies addressing dietary Mg supplementation, in which a 0.6% Mg was also given as a high Mg diet 34‐37 . Our results showed that in the uraemic rats fed a normal Mg (0.1%) a systemic inflammatory response was induced, as deduced from the elevation in the plasma of the pro‐inflammatory cytokines TNF‐α, IL‐1β and IL‐6, which are related to acute‐phase responses and inflammation.…”
Section: Discussionsupporting
confidence: 77%
“…Though a content of 0.05% has been extensively used as normal in rat experimental studies, a slightly higher dietary concentration might be required if the experimental conditions might affect the absorption of Mg. A high dietary phosphate content can reduce the absorption and/or availability of Mg and a decreased magnesium absorption is often found in renal disease (33). Similarly to our conditions, contents of 0.1% or around has been also stablished as the normal levels in many studies addressing dietary Mg supplementation, in which a 0.6% Mg was also given as a high-Mg diet (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 87%
“…An Mg-deficient diet for 6 weeks altered the gut microbiota and was associated with altered anxiety-like behavior [73]. García-Legorreta et al [76] studied the effect of low and high Mg diets on the modulation of the intestinal microbiota of male Wistar rats. Interestingly, after two weeks, the control and low Mg groups both had higher bacterial diversity than high Mg group.…”
Section: Interaction Between Magnesium and Intestinal Microbiotamentioning
confidence: 99%
“…As the authors concluded for mice with no Mg deficiency, supplementation above recommended Mg intake levels can result in the development of intestinal dysbiosis. Hence, inadequate dietary Mg consumption may increase the capacity to harvest energy from the food [76].…”
Section: Interaction Between Magnesium and Intestinal Microbiotamentioning
confidence: 99%
“…Minerals are associated with bacterial physiological processes reshaping the gut microbiota’s structure and composition 49 . Fermented dairy products like yogurt are rich in many minerals with a higher bioavailability.…”
Section: Discussionmentioning
confidence: 99%